Previous Homologous and Heterologous Stress Exposure Induces Tolerance Development to Pulsed Light in Listeria monocytogenes - Heinrich, Victoria; Zunabovic, Marija; Petschnig, Alice; Müller, Horst; Lassenberger, Andrea; Reimhult, Erik; Kneifel, Wolfgang (Frontiers in Microbiology, 2016)
As one of the emerging non-thermal technologies, pulsed light (PL) facilitates rapid, mild and residue-free microbial surface decontamination of food and food contact materials. While notable progress has been made in the characterization of the inactivation potential of PL, experimental data available on the tolerance development to the same (homologous) stress or to different (heterologous) stresses commonly applied in food manufacturing (e.g. acid, heat, salt) is rather controversial. The findings of the present study clearly indicate that both the homologous tolerance development against PL as well as the heterologous tolerance development from heat to PL can be triggered in Listeria monocytogenes. Further, conducted kinetic analysis confirmed that the conventionally applied log-linear model is not well suited to describe the inactivation of L. monocytogenes, when exposed to PL. Instead, the Weibull model as well as the log-linear + tail model were identified as suitable models. Transmission Electron Microscopic (TEM) approaches allow suggestions on the morphological alterations in L. monocytogenes cells after being subjected to PL.